Organizing God’s Work - Harris, M. author. aut Link
X, 236 p.
Keywords: This book provides an organizational perspective on the local congregations of Christianity and Judaism Churches and Synagogues. It will meet the need of those who work in congregations, clergy and lay people alike for an accessible, non-judgmental analysis of the day-to-day work challenges they face. It will also fill a gap in the literature of four academic fields: Social policy and administration; non-profit and voluntary-sector management; the sociology of religion; and organizational behaviour.